Analysis of Local Government Financial Information Quality Based on Internal and External Factors - I Gusti Ayu Purnamawati; Saarce Elsye Hatane (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2020)
Abstract This study attempts to analyze the quality of local government financial information through internal and external factors. This type of research is a causative research using primary data collected through a questionnaire using a likert scale of 1-5. The location of this research is in Buleleng Regency, Bali Province. The sample of this study consisted of the head of the finance department and the accounting staff at each Regional Work Units, amounting to 45 people. The analytical method used in this research is multiple linear regression. The results showed that the competency and working experience (as internal factors), implementation of accounting information system, the role of internal audit (as external factors) had a positive and significant effect on the quality of local government financial reports However, in the future it is hoped that it can be improved through improvements and guidance in several aspects such as increasing the capacity of government officials regarding a more adequate regional financial accounting information system through improving facilities and infrastructure to support regional financial management to achieve good, transparent and accountable governance.